The Effect of Hybrid Work on Job Satisfaction and Employee Motivation and Its Impact on the Turnover Intention of Corporate Employees in Metro Manila - Lotho, Glenn; Angeles, Robin Lance; de Guzman, Mikhaella; Reyes, Yuan Andrei; Rivera, Mary Samantha Reigne (International Journal of Business and Social Science Research, 2026)
This study explored the effect of hybrid work on job satisfaction and employee motivation and its impact on the turnover intention of corporate employees in Metro Manila. Data were collected from corporate employees working under hybrid work arrangements in Metro Manila using a survey-type questionnaire to assess whether respondents are working in a hybrid work setup, as well as to assess their levels of Job Satisfaction, Motivation, and Turnover Intention. A total of 312 raw responses were collected, and data analysis was conducted using the Structural Equation Model (SEM) through WarpPLS. Results showed that Hybrid Work positively influences both Job Satisfaction and Employee Motivation, showing that employees engaged in hybrid work arrangements exhibit higher satisfaction and motivation levels. However, Job Satisfaction was found to have no significant effect on Turnover Intention, this only suggests that satisfaction alone does not determine an employee’s intention to stay. Conversely, Employee Motivation exhibited a significant negative relationship with Turnover Intention, implying that motivated employees are less likely to leave. Overall, the study concludes that hybrid work enhances job satisfaction and employee motivation while indirectly contributing to turnover intention. Therefore, organizations can leverage hybrid work arrangements not only to enhance employee satisfaction and motivation but also to reduce turnover and improve overall organizational performance.